Case Report: Cesarean Scar Pregnancy in 8 Weeks Pregnancy with History of Recurrent Pregnancy Loss - Apriliyani, Sinta Nur; Adinata, Devin Gifarry; Tjahja, Raden (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Caesarean scar pregnancy is a complication in early pregnancy implants gestational sac in the myometrium and fibrous tissues at the site of a previous uterine scar. Recurrent pregnancy loss defines loss as two or more pregnancies that do not have to be consecutive. This condition presents a substantial risk for severe maternal morbidity and associated with psychological aspects.Case Illustration: Mrs. D 37 years old, G6P2A3 in her 8 weeks pregnancy. With significant lower abdominal pain and vaginal bleeding occurs for two days in the beginning of pregnancy. Blood pressure of 70/50mmHg, pulse rate of 100x/min, respiration rate of 22x/min, temperature of 36,6°C, SpO2 of 100%, hemoglobin of 10,7 gr/dL. Abdominal examination was significant for rebound tenderness on lower abdomen. Transvaginal ultrasound which showed a fetus in uterine cavity and a moderate amount of free fluid in intraperitoneal cavity. Upon surgery, 1000cc of blood was found pooled in the peritoneal cavity, and laceration with length of 2 cm, about 5 cm below the uterine fundus.Conclusions: Caesarian scar pregnancy incident is increasing, as a result of high caesarian delivery rate, so the clinician should always ask for the past obstetrical history, particularly in patient with recurrent pregnancy loss with curettage procedure.Laporan Kasus:Kehamilan Bekas Luka Sesar pada Kehamilan 8 Minggu dengan Riwayat Keguguran BerulangAbstrakPendahuluan: Kehamilan bekas luka caesar adalah komplikasi pada awal kehamilan yang menanamkan kantung kehamilan di miometrium dan jaringan fibrosa di lokasi bekas luka rahim sebelumnya. Keguguran berulang diartikan sebagai keguguran sebagai dua atau lebih kehamilan yang tidak harus terjadi secara berurutan. Kondisi ini menimbulkan risiko besar terhadap morbiditas ibu yang parah dan berhubungan dengan aspek psikologis.Ilustrasi Kasus: Ny. D 37 tahun, G6P2A3 dalam usia kehamilan 8 minggu, dengan nyeri perut bagian bawah yang signifikan dan perdarahan vagina terjadi selama dua hari di awal kehamilan. Tekanan darah 70/50mmHg, denyut nadi 100x/menit, laju pernapasan 22x/menit, suhu 36,6°C, SpO2 100%, hemoglobin 10,7 gr/dL. Pemeriksaan perut nyeri tekan signifikan pada perut bagian bawah. USG transvaginal menunjukkan janin dalam rongga rahim dan sejumlah cairan bebas dalam rongga intraperitoneal. Setelah operasi, ditemukan 1000cc darah menggenang di rongga peritoneum, dan terjadi laserasi sepanjang 2cm, sekira 5cm di bawah fundus uteri.Kesimpulan: Kejadian kehamilan bekas luka caesar semakin meningkat akibat tingginya angka kelahiran caesar sehingga dokter harus selalu menanyakan riwayat obstetri masa lalu, terutama pada pasien dengan keguguran berulang dengan tindakan kuretase.Kata kunci: kehamilan bekas luka sesar, keguguran berulang